Evaluation on Planning, Recruitment and Selection of New Employees Case Study in Bank Syariah Muamalat Indonesia - Basuki, Nanang; Tjakraatmadja, Jann Hidajat (The Indonesian Journal of Business Administration, 2012)
PT Bank Syariah Muamalat Indonesia (BMI) is the second largest Islamic bank in Indonesia. As a leading Islamic bank in market share, BMI challenged to grow and aspires to become the 10th largest bank in Indonesia in 2015 (the end of 2011, assets of BMI is on the order-23). To increase service and to support a rapid business growth, Bank Muamalat has made a commitment to increase physical infrastructure and electronic infrastructure. As many as 177 new outlets and 350 new ATM will be open in 2012. The opening of new infrastructures will be supported by the increase of human resources more than 2.000 employees. The study aim to evaluate the existing planning, recruitment and selection process to get new employees at BMI.Â Based on the facts presented, focus group discussion that involves operation managers and conduct questionnaire instrument from 67 respondens, the solution expected to be applied to repair the process and support business expansion.Based on the results of the analysis has been conducted, this study formulates implementation practices proposals with three main objectives: 1. Improve planning process through empowering application of human resources information system;Â 2. Improve recruitment process through the acceleration of electronic recruitment ; 3. Improved selection process especially in written test and psychological test. Keywords: opening outlets, business performance, new style in planning, recruitment and selection. Â